Treatment of Congenital Gastric Outlet Obstruction due to a Web: A Retrospective Single-center Review. Issue 3 (June 2019) - Gehwolf, Philipp; Hechenleitner, Paul; Sanal, Murat; Profanter, Christoph; Häussler, Beatrice; Härter, Bettina
Abstract : Background: Congenital gastric antral web and congenital pyloric atresia are rare reasons of congenital gastric outlet obstruction (CGOO). Depending on the different forms, the symptoms vary from unspecific epigastric pain to nonbilious "projectile" vomiting, ileus and failure to thrive. Throughout the years, many different treatment options are described, like simple surgical dilatation, incision or excision of the membrane, possibly combined with a pyloroplasty. Patients and Methods: In this retrospective single-center observation study, we present 9 cases with different kinds of webs leading to CGOO. In a time period of 45 years (1970 to 2015) different treatment strategies and limitations of minimal invasive endoscopic treatment on the basis of complications and outcome are discussed. Results: Six patients had an incomplete antrum web. One patient suffered from a complete antrum web. In addition, in 2 patients a complete pyloric web, as well as an incomplete pyloric web was found. During the past 45 years, the treatment options for CGOO due to webs changed, and with the development of smaller and more flexible video endoscopes an endoscopic treatment has become feasible. The treatment strategy and follow-up examination was specific to every patient. Conclusion: On the basis of our review, minimal endoscopic procedures in small newborns and toddlers require a high level of experience. They are technically challenging and need suitable equipment. Overall, endoscopists and pediatric surgeons should equally be prepared for all possible complications in every treatment step. The endoscopic approach to managing this unusual disease may require multiple interventions and is associated with a risk of perforation. Therefore, we are convinced that centers undertaking this treatment modality should be equipped with the proper instrumentation, prepared to perform multiple endoscopic interventions, and supported with an ability to emergently convert to surgery if required.